2018
DOI: 10.1101/487710
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanobiological Conditioning of Mesenchymal Stem Cells Enhances Therapeutic Angiogenesis by Inducing a Hybrid Pericyte-Endothelial Phenotype

Abstract: Stem cell therapies have great promise for revolutionizing treatments for cardiovascular disease and other disorders but have not yet achieved their potential due to poor efficacy and heterogeneity in patient response. Here, we used a novel high throughput screening system to optimize the conditioning of mesenchymal stem cells using a combinatorial set of biochemical factors, pharmacological inhibitors and biomechanical forces. Our studies revealed that a combination of specific kinase inhibitors and a complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 68 publications
0
0
0
Order By: Relevance
“…28 This work demonstrated that mechanical loading with a physiological waveform (brachial waveform) at 7.5% mechanical strain in combination with a EGFR/ErbB2-4 (E/E) inhibitor leads to enhanced MSC production of soluble HGF, increases endothelial cell and pericyte markers, and pericyte-like functionality in MSCs. 28 Using a high throughput biaxial oscillatory stretch system (HT-BOSS) developed in our laboratory, [29][30][31] we explore the effect of these loading conditions on senescence in MSCs derived from aged donors (68-92 years old). We found that mechanical conditioning led to a lasting enhancement of proliferative function, expansion capacity, multipotency, and reduction of senescence in MSCs from aged donors.…”
Section: Introductionmentioning
confidence: 99%
“…28 This work demonstrated that mechanical loading with a physiological waveform (brachial waveform) at 7.5% mechanical strain in combination with a EGFR/ErbB2-4 (E/E) inhibitor leads to enhanced MSC production of soluble HGF, increases endothelial cell and pericyte markers, and pericyte-like functionality in MSCs. 28 Using a high throughput biaxial oscillatory stretch system (HT-BOSS) developed in our laboratory, [29][30][31] we explore the effect of these loading conditions on senescence in MSCs derived from aged donors (68-92 years old). We found that mechanical conditioning led to a lasting enhancement of proliferative function, expansion capacity, multipotency, and reduction of senescence in MSCs from aged donors.…”
Section: Introductionmentioning
confidence: 99%